Unity 2018 augmented reality projects : build four immersive and fur AR applications using ARKit, ARCore, and Vuforia - Glover, Jesse (Packt Publishing, 2018)
Augmented Reality offers the magical effect of blending the physical world with the virtual world. On the other hand, Unity is now the leading platform to develop augmented reality experiences since it provides a great pipeline to work with 3D assets. This book will educate you about the specifics of augmented reality development in Unity 2018.